Virologic study of fatal cases of paralytic poliomyelitis - Celiz G., Eduardo (1968)
Virological study 6 fatal cases of poliomyelitis was made, having poliovirus isolated from different organ samples taken during the autopsy. Poliovirus Type I. mesenteric ganglion marrow, large intestine, liver, spleen was isolated. Poliovirus type II, bone, intestine, rectal scraping. Poliovirus Type III marrow, mesenteric ganglion, large intestine, small intestine, liver, spleen and kidney.